Soal Matematika Berkonteks Budaya Daerah yang Diajukan Mahasiswa Calon Guru Sekolah Dasar - Saleh, Sitti Fithriani; Ernawati, Ernawati; Mardawati, Mardawati; Anugrah, Wanda Rezki (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
The purpose of this study was to conduct initial identification of mathematical problems in the context of local culture proposed by students. A total of 17 prospective elementary school teacher from a private university in Makassar were the subjects of this study. Students were asked to pose mathematical problems about the Greatest Common Factor (GCF) of two natural numbers and include the local cultural context. The results showed that of the 17 mathematical problems, 15 problems classified as solvable and two problems classified as unsolvable. Mathematical problems could not be solved because there was less information in the problems or there was conflicting information. The local cultural context used in the mathematical problems was dominated by the Bugis-Makassar ethnic group. Of the 17 mathematical problems posed, 16 problems were classified as real problems and one problem was classified as a pseudo problem. The problem was classified as pseudo problem because it contained contexts that were not relevant to the actual situation.